Morphometric correlates of host specificity in Dactylogyrus species (Monogenea) parasites of European Cyprinid fish - Simková, A; Desdevise, Y; Gelnar, M; Morand, S (Parasitology, 2001)
We test the hypothesis that living on larger fish may impose constraints, i.e. the need to develop large attachment organs, related to the necessity to remain attached on large gills. For this, we compiled data on body size and morphometric measurements of attachment organs of 44 Dactylogyrus species (ectoparasites with direct life-cycle) from 19 cyprinid species. Nineteen dactylogyrid species were considered as specialists (infecting only 1 host species) and 25 as generalists (infecting more than 1 species). The lack of phylogenetic information lead us to perform comparative analyses using raw values and independent contrasts obtained by random phylogenies. Our results show that rich parasite communities are formed by specialists and generalists whereas poor communities are composed mainly of generalist parasites. Moreover, specialists are found on larger hosts, which may reflect a specialization on a predictable resource, as larger fish live longer and offer large gills for parasite colonization. Parasite specialization is shown to be linked with adaptation of attachment organs to their fish hosts. Two morphometric variables of the attachment organ, the total length of anchor and length of base of anchor, were positively correlated with host length for specialists.
Keywords: Animals; Trematoda; Gills; infekce červy třídy Trematoda; Trematode Infections; druhová specificita; Slovakia; nemoci ryb; infestace ektoparazity; Ectoparasitic Infestations; Host-Parasite Interactions; Fish Diseases; máloostní; interakce hostitele a parazita; Species Specificity; žábry; Phylogeny; Czech Republic; Česká republika; Cypriniformes; Slovenská republika; zvířata; fylogeneze